Primary optic nerve sheath schwannoma: A case report and literature review - Meriam Benzalim, MD; Hermann Ondima, MD; Soumaya Alj, PhD (Radiology Case Reports, 2023)
Schwannomas are benign tumors of the peripheral nervous system that arise from Schwann cells. Intracranial schwannomas most commonly arise from the vestibulocochlear nerve, followed by the fifth nerve. However, optic nerve sheath schwannomas are very rare due to the lack of Schwann cells on it. A few exceptional cases of optic nerve sheath schwannoma have been described in the literature. In this article, we report a rare case of primary optic nerve sheath schwannoma in a 48-year-old woman who presented with progressive visual loss and left-sided proptosis. Magnetic resonance imaging revealed a well-demarcated intraconal orbital mass with cystic appearance and rim enhancement. The diagnosis of optic nerve schwannoma was proposed and confirmed histologically after surgical resection.